2009
DOI: 10.3354/ab00131
|View full text |Cite
|
Sign up to set email alerts
|

In situ evidence for pre-capture qualitative  selection in the tropical bivalve Lithophaga simplex

Abstract: Few feeding studies have been performed on tropical bivalves, and in situ feeding studies are lacking altogether. We investigated retention efficiencies for natural particles in the coralboring tropical mytilid Lithophaga simplex. Using the in situ InEx technique (Yahel et al. 2005; Limnol Oceanogr Methods 3:46-58) SCUBA divers collected samples from the water inhaled and exhaled by undisturbed bivalves at the coral reef of Eilat (Gulf of Aqaba). Particle retention efficiencies were determined using flow cytom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 67 publications
2
44
0
1
Order By: Relevance
“…However, note that the capture mechanism changes from ciliary downstream collecting in veliger larvae (see 'Ciliary downstream collecting') to cirri trapping during the postlarval development of most bivalves (e.g. Cannuel et al 2009) Finally, it should be emphasized that qualitative selection in suspension-feeding bivalves has been assumed to be exclusively post-capture, but in the tropical bivalve Lithophaga simplex studied by Yahel et al (2009), qualitative selection occurs prior to retention. This encourages a re-examination of what is meant by 'retention'.…”
Section: Suspension-feeding Without Laterofrontal Cirrimentioning
confidence: 99%
“…However, note that the capture mechanism changes from ciliary downstream collecting in veliger larvae (see 'Ciliary downstream collecting') to cirri trapping during the postlarval development of most bivalves (e.g. Cannuel et al 2009) Finally, it should be emphasized that qualitative selection in suspension-feeding bivalves has been assumed to be exclusively post-capture, but in the tropical bivalve Lithophaga simplex studied by Yahel et al (2009), qualitative selection occurs prior to retention. This encourages a re-examination of what is meant by 'retention'.…”
Section: Suspension-feeding Without Laterofrontal Cirrimentioning
confidence: 99%
“…This seemingly paradoxical situation is thought to arise because coral reefs are efficient at trapping nutrients, bacteria, zooplankton, and phytoplankton from the surrounding waters (Ayuki 1995;Yahel et al 1998;Holbrèque et al 2006) and so can balance the nutrients required for primary production and their leakage offshore ). Because many reefs depend on suspended particles and dissolved nutrients trapped from the flowing water, their functioning may be regulated by the hydrodynamics.…”
mentioning
confidence: 99%
“…These studies yielded seminal information which would become at once a foundation and a prism through which we have continued to interpret the characteristics of bivalve feeding, and indeed the techniques are important tools in the panoply we use today. Adaptation of this approach to measurement in the field, either indirectly (via the biodeposition method, Cranford et al 1998, Iglesias et al 1998, Cranford & Hill 1999 or pumping from the field site to experimental chambers, MacDonald & Ward 1994) or directly (the InEx method, Yahel et al 2003Yahel et al , 2005Yahel et al , 2006Yahel et al , 2009 this Theme Section) has allowed us to extend these observations much closer to the natural habitat. Simultaneously, application of the physical principles of fluid mechanics has yielded important insights into the hydrodynamic principles of particle movement underlying suspension feeding in bivalves (Jørgensen 1981, 1982, 1983, Jør-gensen et al 1984, Nielsen et al 1993, Riisgård & Larsen 2001.…”
Section: Introductionmentioning
confidence: 99%
“…(3) Pre-capture selection (Yahel et al 2009). Qualitative selection in suspension-feeding bivalves has been assumed to be exclusively post-capture, but in the tropical species studied by Yahel et al 2009, qualitative selection is shown to occur prior to retention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation